Characterization of distinct polycystic ovary syndrome subtypes by cluster and principal component analyses - Burns, Kharis A.; Stuckey, Alexander W.; Wilson, Scott G.; Watts, Gerald F.; Stuckey, Bronwyn G. A. (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is a common, but clinically heterogeneous, condition. This study explores PCOS subtypes using two orthogonal statistical analyses of biochemical and anthropometric data.MethodsUnsupervised hierarchical cluster analysis and principal component analysis (PCA) of hormonal and metabolic parameters were performed in a cohort of PCOS-affected women, diagnosed based on the NIH criteria. Data collected included body mass index (BMI), blood pressure (BP), fasting insulin and glucose (HOMA-IR), gonadotropins, androgens, and lipids. Subtypes were explored using unsupervised hierarchical cluster analysis, grouping both phenotypic variables and patients into clusters. PCA resolved correlated variables (excluding BMI) into independent factors, and the influence of BMI on the components was then explored.ResultsOne thousand and thirty-five women with PCOS were included in the study, with 975 assessed using cluster analysis and PCA. Two main clusters of variables were evident: one characterized by BP, BMI, HOMA-IR, and lipids (triglycerides/cholesterol/LDL) and the second by LH: FSH, androgens, SHBG, and HDL. Three separate patient clusters emerged: cluster A (29.6% of women) showed higher BP, BMI, HOMA-IR, and lipids (triglycerides/cholesterol/LDL) and lower LH: FSH, SHBG, and HDL. Cluster C (43.3%) showed lower BP, BMI, HOMA-IR, triglycerides, testosterone, and FAI and higher LH: FSH, DHEAS, androstenedione, 17-hydroxyprogesterone, SHBG, and HDL. Cluster B (27.1%) was intermediate. Two components aligned with the cluster analysis: principal component (PC) 1, including HOMA-IR, systolic and diastolic BP, triglycerides, LDL, FAI, and SHBG, was positively correlated with BMI (R2= 0.32, p-value < 0.0001) and aligned with cluster A. PC2, influenced by testosterone, LH: FSH, FAI, DHEAS, androstenedione, and 17-hydroxyprogesterone, with loadings in the opposite direction from LDL and cholesterol, aligned with cluster C, with little relationship with BMI (R2= 0.0067, p-value = 0.0107).DiscussionDifferent metabolic and reproductive PCOS subtypes are evident. Androstenedione and 17-hydroxyprogesterone are important in the reproductive phenotype, highlighting the importance of these hormones in diagnosis and subtype identification and emphasizing their significance in understanding PCOS biology as a predominantly hyperandrogenic disorder. BMI influences and exacerbates the metabolic subtype; in the reproductive group and in lean/normal BMI patients, there is little relationship between weight and other PCOS-related characteristics. Accordingly, traditional treatment paradigms cannot be generalized to all women, and these subtypes may ultimately be viewed as separate disorders